Successful implementation of teaching factory in machining expertise in vocational high schools - Bernardus Sentot Wijanarka; Fendy Wijarwanto; Patterson Nji Mbakwa (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2023)
This research aims to (1) evaluate the application of the teaching factory (Tefa) in the field of machining expertise in Vocational High Schools (VHSs) and (2) identify the obstacles to the implementation of Tefa. The research uses the CIPP (Content, Input, Process, and Product) evaluation method. This research was carried out in four vocational schools on the competence of machining expertise with the criteria of having implemented Tefa for more than five years and as a pioneer in implementing Tefa. The four schools are Vocational High School (VHS) Mikael Surakarta, State Vocational High School (SVHS) 1 Magelang, SMK Warga Surakarta, and SMK Karya Teknika Colomadu Karanganyar. The research respondents are principals, vice principals, heads of competency skills, and managers of Tefa. The data collection was through interviews, observation, and document scrutiny. The instruments used are an interview guide, observation sheet, and document analysis guide. The qualitative data analysis used qualitative data processing software. The results are as follows. (1) The application of Tefa in VHSs based on the evaluation is the context component 98%, the input component 89.25%, the process component 87%, and the product component 82.5 %. The percentage of evaluating the implementation of Tefa as a whole for the CIPP component is 89.2%, or very good; and (2) The obstacles faced in implementing Tefa in vocational high schools include rules for product sales, rules for working hours for public teachers, setting practicum schedules, working hours that were not flexible, rapid technological changes, understanding of block schedules, and lack of human resource competence. The results of this study imply that schools that implement Tefa are expected to be well-managed because it impacts the progress of VHS processes and products.